Regional Differences in the Conditions of Technological Progress in Europe - Csugány, Julianna; Tánczos, Tamás (Naše gospodarstvo/Our economy, 2020)
The spatial structure of the world is unequal, centres and peripheries alternate. There are significant social and development differences between countries in the world, but there is also an unequal development within the countries. The main purpose of the regional policy is to reduce spatial inequalities by catching up the underdeveloped areas. Nowadays, in the era of the Fourth Industrial Revolution, technological progress creates possibilities for developing regions to catch up, because new technologies require new skills that are less dependent on factor endowments of countries. Most economies are unable to create new technologies because they do not have the appropriate resources or their institutional environment does not favour innovation. However, technological progress can also be observed in these countries by adopting and applying new technologies effectively. This research aims to illustrate the regional differences in the conditions of technological progress in Europe, using multivariate statistical methods. Based on the European Regional Competitiveness Index, the research question to be analysed is whether new technologies may be able to decrease spatial differences. We compare the European regions in the field of innovation in order to highlight the critical areas that can promote or prevent the reduction of inequalities.